Measuring the importance of the uniform nonsynchronization hypothesis - Dias, Daniel (2022)
In this paper we critically reappraise some measures of the importance of time- dependent price setting rules and propose an alternative way to gauge the signi - cance of this type of price setting behaviour. The merits of the proposed measure are highlighted in an application using micro-data. Our results suggest that a large proportion of price trajectories may be compatible with simple time-dependent price setting mechanisms but the strength of this evidence very much depends on the way that is used to evaluate the importance of this type of behaviour.